Does corporate tax avoidance explain firm performance? Evidence from an emerging economy - Nguyen Vinh Khuong; Nguyen Thanh Liem; Phung Anh Thu; Thai Hong Thuy Khanh (Cogent Business & Management, 2020)
Corporate tax avoidance is an act aiming at reducing tax amount liable to the government, which is expected to raise firm value. However, agency theory postulates that opportunistic managers can lower tax liabilities through the arrangement of complex transactions, enabling them to shirk or pursue own interests. Therefore, the need to examine the link between corporate tax avoidance and firm performance is evident, yet there has not been any research on this in the context of Vietnam, a country plagued with tax-avoiding cases. We are the first to examine the empirical link using a sample of Vietnamese listed firms over the period from 2010 to 2016, using a wide-ranging set of performance and tax-sheltering indicators. Overall, the results indicate a mixed relationship between corporate tax avoidance and firm performance in Vietnam.
Keywords: M40; M48; K34; 650; Corporate tax avoidance; firm performance; Vietnam